Mengungkap Perilaku Wajib Pajak Orang Pribadi dengan Pelaporan Sistem E-Filing Lintas Generasi - Tia Mahrurotul Fikriyah; Sri Trisnaningsih (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Individual taxpayer compliance in Indonesia is still relatively low. The government launched an e-filing system with the aim of providing convenience in tax reporting. Across generations, there are still different responses to utilizing information technology. This study aims to reveal the obedient behavior of individual taxpayers (WPOP) with the existence of a cross-generational e-filing system. Qualitative methods were used in this study with a phenomenological approach. The phenomenological approach is intended to examine the problem of the current phenomenon. There are 8 informants in the category of individual taxpayers who work at ABC Hospital and are from two generations, namely the X generation and the millennial generation. The results of this study indicate that with the e-filing system, individual taxpayers are more obedient and timely in submitting annual tax returns (SPT). Especially for the millennial generation, who are already familiar with technological developments However, there are obstacles in generation X, namely the speed of adopting information technology, which is still lacking. So, in the reporting of SPT through e-filing, there are still some who need assistance with the implementation of the system. The novelty of this research is that it uses cross-generation to reveal obedient behavior in tax reporting. Keywords: Behavior, WPOP, E-Filing System, Millennial Generation, and Generation X